Recovery rates of bottlenose dolphin (Tursiops truncatus) carcasses estimated from stranding and survival rate data. Issue 1 (4th September 2015) - Carretta, James V.; Danil, Kerri; Chivers, Susan J.; Weller, David W.; Janiger, David S.; Berman‐Kowalewski, Michelle; Hernandez, Keith M.; Harvey, James T.; Dunkin, Robin C.; Casper, David R.; Stoudt, Shelbi; Flannery, Maureen; et al.
Abstract: Recovery of cetacean carcasses provides data on levels of human‐caused mortality, but represents only a minimum count of impacts. Counts of stranded carcasses are negatively biased by factors that include at‐sea scavenging, sinking, drift away from land, stranding in locations where detection is unlikely, and natural removal from beaches due to wave and tidal action prior to detection. We estimate the fraction of carcasses recovered for a population of coastal bottlenose dolphins ( Tursiops truncatus ), using abundance and survival rate data to estimate annual deaths in the population. Observed stranding numbers are compared to expected deaths to estimate the fraction of carcasses recovered. For the California coastal population of bottlenose dolphins, we estimate the fraction of carcasses recovered to be 0.25 (95% CI = 0.20–0.33). During a 12 yr period, 327 animals (95% CI = 253–413) were expected to have died and been available for recovery, but only 83 carcasses attributed to this population were documented. Given the coastal habits of California coastal bottlenose dolphins, it is likely that carcass recovery rates of this population greatly exceed recovery rates of more pelagic dolphin species in the region.